"Barriers to growth in small firms / edited by J. Barber, J. S. Metcalfe and M. Porteous" - "Barber, J. (ed.) ; Metcalfe," (London, 1989)
This book examines both the growth and the barriers to growth of small firms. It examines market and industrial structures, the role of investment institutions and their handling of small business accounts. This book should be of interest to professionals in small business, students and researchers in business studies and economics.
Keywords: Small business groeth